Pengaruh Waktu Praperlakuan Sari Buah Mengkudu Terhadap Wujud Efek Toksik Teofilin Pada Tikus Putih Jantan - Sari, Sant Purna; Donatus, Imono A (UI Scholars Hub, 2006)
The use of traditional medicine in Indonesia as the substitution and complementary of modern medicine for the treatment of disease may cause interactions to other therapeutic drugs in the body. This research was aimed to observe the effect of Morinda juice on theophyllin toxicity in white rats. This research was initiated by checking sample of Morinda juice including organoleptic, density and thin layer chromatography analysis. The effect of pre-treatment time of Morinda juice to theophyllin toxicity was done by taking randomized completely design using 60 male Sprague Dawley rats that were devided randomly into 5 groups. First group (control) was given 225 mg/kg BW theophyllin suspension, second to fourth groups were given 5.5 g/kg BW Morinda juice on 2, 6, 12, and 24 hours before treatment of theophyllin, then all were observed the toxic effect that appeared. The results of interaction effect have shown that the pre-treatment of Morinda juice which was given 2, 6, 12, and 24 hours before 225 mg/kg BW theophyllin increased number of rats death for 40, 60, 60, and 100%.